2006
DOI: 10.1016/j.susc.2006.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Surface and transport properties of Au–In liquid alloys

Abstract: Thermodynamic quantities on Au-In liquid alloys have been used as the input data for the interaction parameter calculations in the framework of the complex formation model (CFM). Once the interaction energies are computed the surface (surface tension and surface composition) and transport properties (chemical diffusion and viscosity) as well as the microscopic functions (concentration fluctuations in the long-wavelength limit and chemical short-range order parameter) have been calculated. The concentration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Gibbs energy of mixing in the binary Au-In system has been reported by several groups. It was shown that the normalized Gibbs free energy of mixing (GM/RT), under the conditions similar to our NW growth system, has a minimum value of almost −3 at 45.5% In composition, 28 which indicates that the alloying of Au and In lowers the energy of the catalyst significantly. Also, the Au and In alloy is known to show extremely rapid inter-diffusion.…”
Section: Resultssupporting
confidence: 53%
“…Gibbs energy of mixing in the binary Au-In system has been reported by several groups. It was shown that the normalized Gibbs free energy of mixing (GM/RT), under the conditions similar to our NW growth system, has a minimum value of almost −3 at 45.5% In composition, 28 which indicates that the alloying of Au and In lowers the energy of the catalyst significantly. Also, the Au and In alloy is known to show extremely rapid inter-diffusion.…”
Section: Resultssupporting
confidence: 53%
“…Most of the variables used were found in literature and are explained in more detail in the Supporting Information. The solid–liquid energy of the nucleus was initially varied as a fitting parameter.…”
mentioning
confidence: 99%
“…Surface Energy Estimation . On the basis of the composition, we estimated the surface tension based on linear combination of the surface energy of Au and Ga . By sorting the collected data depending on the interface morphology (truncated or flat corner), we fitted the solid–vapor surface energy, based on the surface tension, to agree with our observations.…”
Section: Methodsmentioning
confidence: 68%
“…Assuming that the imaging of the droplet is a two-dimensional projection of a spheroidal cap, and that any change in droplet volume relates to Ga concentration, this allows for an estimation of the droplet composition for each frame of interest. From the composition, the surface tension is estimated by linear extrapolation from the pure species (Au and Ga), and details on the estimation are provided as Supporting Information. Each extracted data point is then related to whether a truncation has occurred recently (within 0.5 s), presented as green or black in Figure .…”
mentioning
confidence: 99%